Application of a quartz crystal microbalance to measure the mass concentration of combustion particle suspensions. (November 2019) - Kaur, Kamaljeet; Mohammadpour, Raziye; Jaramillo, Isabel C.; Ghandehari, Hamidreza; Reilly, Christopher; Paine, Robert; Kelly, Kerry E.
Abstract: Researchers studying the biological effects of combustion particles typically rely on suspending particles in de-ionized (DI) water, buffer, and/or media prior to in vitro or in vivo experiments. However, the hydrophobic nature of combustion particles makes it difficult to obtain well-suspended, evenly dispersed mixtures, which also makes it difficult to obtain equivalent dosing and endpoint comparisons. This study explored the use of a quartz crystal microbalance (QCM) to measure the mass concentration of combustion particle suspensions. It compared the QCM mass concentration to that estimated by placing a known mass of combustion particles in DI water. It also evaluated the effect of drop volume and combustion particle type on QCM measurements. The results showed that QCM is a promising direct method for measuring suspended combustion particle mass concentrations, and it is particularly effective for quantifying concentrations of difficult-to-suspend particles and for combustion particles placed in polystyrene containers, which can lead to substantial particle losses. Highlights: QCM allows precise mass concentration measurements of combustion particle suspensions. Substantial particle loss can occur due to particle-wall interactions. QCM allows estimation of dissolved organic fraction of a suspension.